Attitude of Private School Teachers towards Teacher Eligibility Test, India - Murugan, S. (Journal of Education and Vocational Research, 2014)
Now-a-days the teacher education has some lack in quality. Because, the outcome of the quality teacher in teacher education colleges is low; some private management does not consider the quality of education and they depend on earning money. The present study investigates attitude of private school teachers towards Teacher Eligibility Test (TET). The tool of Attitude towards TET was constructed and standardized by the investigator. The data were collected from 327 private school teachers in Thanjavur District, India and simple random technique was used for the study. This study reveals that the attitude of private school teachers have high TET attitude and the private school teachers attitude is not significant with respect to gender, locality. Furthermore there is a significant difference in TET attitude between rural and urban area school teachers.